2022
DOI: 10.3390/agriculture12060849
|View full text |Cite
|
Sign up to set email alerts
|

Rapeseed Meal and Its Application in Pig Diet: A Review

Abstract: Rapeseed is the second largest plant protein resource in the world with an ideal profile of essential amino acids. Rapeseed meal (RSM) is one of the by-products of rapeseed oil extraction. Due to the anti-nutritional components (glucosinolates and fiber) and poor palatability, RSM is limited in livestock diets. Recently, how to decrease the anti-nutritional factors and improve the nutritional value of RSM has become a hot topic. Therefore, the major components of RSM have been reviewed with emphasis on the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 88 publications
(74 reference statements)
0
7
1
Order By: Relevance
“…As mentioned above, rapeseed is a very common crop that is not genetically modified [ 73 ]. Moreover, even though some studies show that the weight gained is comparable to or a little lower than that observed with traditional feeding, the feed conversion ratio is significantly improved [ 4 , 73 ]. Furthermore, dietary FRSM can prevent intestinal dysbiosis in weaners [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned above, rapeseed is a very common crop that is not genetically modified [ 73 ]. Moreover, even though some studies show that the weight gained is comparable to or a little lower than that observed with traditional feeding, the feed conversion ratio is significantly improved [ 4 , 73 ]. Furthermore, dietary FRSM can prevent intestinal dysbiosis in weaners [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, more than 83.14 million metric tonnes of rapeseed are produced worldwide [ 2 ]. However, besides its relatively good protein composition, some components such as oxazolidinethione, isothiocyanates, thiocyanates, glucosinolate-derived nitriles, tannins and phytic acid, which limit the utilization of basal nutrients, are also present in RSM [ 3 , 4 ]. Feeding trials have shown that the glucosinolates present in rapeseed press cake reduce feed intake and weight gain in experimental pigs [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, studies on the chemical composition of RSM highlight the relatively high protein content compared to the meals of other major oilseed crops, except soybean (Enami, 2011). Oilfree rapeseed meal contains 35-40% crude protein (Nesi et al, 2008;Sanjayan et al, 2014;Cheng et al, 2022). Although it is comparable in protein with soybean meal, but due to the presence of antinutritional factors including fiber content it has a generally lower digestibility (Khajali and Slominski, 2012).…”
mentioning
confidence: 99%
“…Since then, selection has been more limited and has mainly focused on reducing fibre content in favour of protein content, with little effect on the composition of industrial meal. Thus, the main components of rapeseed meal have been reviewed with emphasis on the methods of improving the nutritional value (Cheng et al, 2022). However, the chemical composition of RSM can be changed between rapeseed and canola type (Tab.…”
mentioning
confidence: 99%